A NOVEL APPROACH FOR SHIPPING CONTAINER CODE RECOGNITION - Lê Hoàng Thanh (Tạp chí Khoa học Đại học Đà Lạt)
Optical character recognition is the mechanical or electronic conversion of images of typed, handwritten or printed text into machine-encoded texts, whether from a scanned document, a photo of a document, a scene-photo or from subtitle text superimposed on an image. It is widely used as a form of information entry from printed data records including, passport documents, invoices, bank statements, computerized receipts, business cards, mail, printouts of static-data, or any suitable documentation. Currently, in logistic, container code recognition is mainly done manually, so it is necessary to have a solution for automatic identification to save time and effort. This paper proposes a novel model for code recognition which can be applied for shipping containers widely used in logistics. The obtained experimental results have proved that the proposed model produces satisfactory confidence on a benchmark dataset.